Room temperature sintering of polar ZnO nanosheets: I-evidence. Issue 25 (20th June 2017) - Fernández-Pérez, Amparo; Rodríguez-Casado, Verónica; Valdés-Solís, Teresa; Marbán, Gregorio
Abstract : Unambiguous evidence of the spontaneous loss of surface area at room temperature in polar ZnO. Abstract : Polar ZnO nanosheets of a high specific surface area (∼120 m 2 g −1 ) were subjected to storage under different atmospheres at room temperature and analyzed for changes in their textural and crystal properties. During their storage under laboratory conditions (in closed transparent polypropylene vials kept under the light of the laboratory on worktop tables) the nanosheets lost up to 75% of their specific surface area in approximately two months, with most of the loss occurring during the first two weeks. The narrow mesoporosity (∼5 nm pore size) became filled with ZnO during the process. No loss or gain in weight was detected. The loss of specific surface area took place under all of the atmospheres assayed, in the following order: moist air (with or without light) > moist CO2 -free atmosphere (with or without light and/or oxygen) > dry CO2 -free oxygen-containing atmosphere (with or without light) > dry inert atmosphere (with light) > dry inert atmosphere (in the dark). During storage the ZnO crystals grew mainly by the partial merging of their polar surfaces in a process triggered by the action of moisture, oxygen and, in the absence of these two agents, light. The mechanism of this intriguing phenomenon will be analyzed in detail in the second part of this work.